Bidirectional two-sample Mendelian randomization study of causality between rheumatoid arthritis and myocardial infarction - Guo, Hao-Yang; Wang, Wei; Peng, Hui; Yuan, Hui (Frontiers in Immunology, 2022)
Background Epidemiological evidence suggests an association between rheumatoid arthritis (RA) and myocardial infarction (MI), but causality remains uncertain. Therefore, the purpose of our study was to explore the causal association between RA and MI. Methods Using publicly available genome-wide association study (GWAS) summary datasets, Bidirectional two-sample Mendelian randomization (TSMR) was performed using inverse-variance weighted (IVW), weighted median (WME), MR-Egger regression, Simple mode, and Weighted mode. Results TSMR results for causal effect of RA on MI (IVW, odds ratio (OR) =1.041, 95% CI: 1.007 ~ 1.076, P=0.017; WME, OR =1.027, 95% CI: 1.006 ~ 1.049, P=0.012) supported the causal association between RA and increased risk of MI; TSMR results for causal effect of MI on RA (IVW, OR =1.012, 95% CI: 0.807 ~ 1.268, P=0.921; WME, OR =1.069, 95% CI: 0.855 ~ 1.338, P=0.556) indicated that there was no causal association between MI and increased risk of RA. Conclusion Bidirectional TSMR analysis supports the causal association between RA and increased risk of MI but does not support the causal association between MI and increased risk of RA.